Case Report: The nonsense variation of the cardiac transcription factor NKX2-5 has been identified in a Chinese family with nonsyndromic congenital heart disease - Zhang, Haixia; Chen, Jing; Wang, He; Xiang, Qinqin; Liu, Shanling (Frontiers in Genetics, 2025)
BackgroundNK2 HOMEOBOX 5(OMIM: 600584, NKX2-5), a pivotal cardiac regulatory transcription factor, represents the initial identified genetic etiology underlying congenital heart diseases (CHDs). As a member of the NK homeobox gene family, NKX2-5 functions as an essential DNA-binding transcriptional activator. It demonstrates robust expression levels in both primary and secondary heart fields’ cardiac progenitor cells, playing an indispensable role in cardiovascular development. Here we reported a NKX2-5 nonsense variant in a Chinese family with nonsyndromic congenital heart disease.Case presentationTrio-whole-exome sequencing (Trio-WES) was performed on the proband and parents, followed by Sanger sequencing for verification and linkage analysis using available DNA samples from this family and additional family members. A nonsense variant (NM_004387.4: c.342C>A, p.(Cys114*)) was identified within the NKX2-5 gene through Trio-WES analysis and classified as likely pathogenic according to the criteria of the ACMG. Sanger sequencing revealed the presence of this nonsense variant in all affected family members (II1, II3, III1, and III5) within the NKX2-5 gene, while unaffected family members (II2, II7, and II8) did not exhibit this variant.ConclusionThe present study identified a heterozygous nonsense variant of the NKX2-5 gene in a family with nonsyndromic congenital heart disease, suggesting that this variant may be the underlying cause of the disease within this particular family. Our findings suggests that it can cause diverse phenotypes and varying severity of cardiac abnormalities even within the family. Additionally, an early and definitive genetic diagnosis can provide precise information for subsequent treatment and fertility counseling.